Recidiva em lesão central de celulas gigantes : revisão sistemática e meta-análise - Pontes, Caetano Guilherme Carvalho (2015)
Central giant cell granuloma (CGCG) is an uncommon pathology of the maxillary bones, which has diverse clinical behavior. It can be treated either by surgical removal or by conservative methods such as systemic daily application of calcitonin and intralesional injections of corticosteroids. Recurrence of lesions seems to vary according to its clinical behavior, location and treatment modality. The aim of this study was to evaluate the recurrence rate of the CGCG of the jaws and its associated factors through a systematic review and meta-analyses. An electronic search in PubMed and Scopus databases was conducted in order to identify observational studies, published in English, that reported the recurrence rate of CGCG of the jaws regardless of treatment modality. In addition, a hand search of cross-references was also carried out identify additional studies. We excluded studies that did not report the main outcome of interest, with less than five cases and studies not available for full text review. Twenty-one studies, published between 1973 and 2011 met eligibility criteria and were included in this review. We observed a global recurrence rate of 13.4% (8.4%-19.1%, 95% CI). Surgical curettage showed the higher recurrence rate (15.8%, 10.7 – 21.7 95%CI), followed by calcitonin administration (9.7%, 0.0 – 31.8 95% CI) and surgical resection (0.16%, 0.0 – 0.07 95%CI). Lesion location was not associated with a higher risk of recurrence (RR = 1.7, 0.97 – 2.9, 95% CI). The results of this systematic review showed a high risk of lesion recurrence of aggressive CGCG treated with surgical curettage.